Cartografia de um processo: o processo criativo do espetáculo Saga no Sertão da Farinha Podre do coletivo Teatro da Margem - Araújo, Getúlio Góis de (2012)
This memorial proposes the cartography (mapmaking) on the creative process of the play Saga no Sertão da Farinha Podre , by Coletivo Teatro da Margem, directed by Narciso Telles. To map the genesis of the play creation, firstly I accompanied the process as the Director Assistant, registering on photos, vídeos and writing, the most significant impressions of being immersed in na artistic process. Secondly, I opted for a textual form which would point conceptual issues related to the mentioned process and which would be as subjetive as the artistic exercise itself. Therefore, we propose the subjectivation of the creative process registrations, considering not only the affection during the registration process as well as the act of rebuilding it.